EDUCATION QUALITY MANAGEMENT SYSTEM OF SECONDARY SCHOOLS - Yakubova Mukhtaram Abdumavlyanovna (Galaxy International Interdisciplinary Research Journal, 2021)
It is critical that enhancing accountability in the education sector and promotes the importance of mutual accountability between schools and communities for their overall improvement on key indicators so as to enhance teaching and learning in schools. Improvement in teaching and learning requires a radical approach underpinned by quality and efficiency at school and district level. Performance management is a key process in any school / district and should assist the management and staff to focus on key issues and objectives to ensure sustainability and improvement in delivering quality education.This article discusses about the education quality management system of secondary schools.